Effect of salinity stress on Dill seeds germination and growth in vivo in Libya - Sayed Ewase, Alaa El-din; Abobakr, Akareb; Benail, Hawa; Imhammed, Mariam (Scientific Journal of University of Benghazi, 2026)
The aim of this study is to detect the effect of salinity stress on Dill (Anethum graveolens) seeds germination and growth in vivo in Libya. For this purpose, five treatments of different concentrations of NaCl were used. The following parameters: Seeds germination, roots number and length, plant length, number of leaves, plant strength, shoot tip necrosis and the percentage of survivals were recorded. The Obtained results showed that all growth parameters were reduced by increasing NaCl concentration. In the same time, The percentage of shoot tip necrosis was increased with a significant differences among all treatments. In a parallel study, the results observed that Dill (Anethum graveolens) plants were more salt-tolerant than Coriander (Coriandrum sativum) plants, where they resist salinity till 4000 ppm NaCl, while Coriander plants resist till 3000 ppm NaCl only.